UV-curable fluorine-containing hybrid coatings via thiol-ene click reaction and an in situ sol-gel method - ÇAKMAKÇI, EMRAH; KAHRAMAN, MEMET VEZİR (SPRINGER, 2013)
In this study, photocurable fluorine-containing coatings were prepared via thiol-ene click chemistry and an in situ sol-gel method. MPTMS was used as a coupling agent to perform both the thiol-ene click reaction and the sol-gel reactions. PFOTES was utilized for the preparation of fluorine-containing coatings. The addition of fluorine and silica showed a significant impact on the properties of the coatings. The addition of silica greatly enhanced the mechanical properties of the coatings. As the fluorine and silica contents were increased in the formulations, flame retardancy, hydrophobicity, and oleophobicity of the coatings increased. High char yields were obtained for the silica- and fluorine-containing samples. Furthermore, the effect of Al2O3 nanoparticles on the properties of the hybrid coatings was investigated.
Keywords: Hydrophobe; Thiol-ene click reaction; Fluorine; Al2O3; Sol-gel; FUNCTIONALIZATION; POLYMERS; SCRATCH; SILICA